2020
DOI: 10.1093/scan/nsaa155
|View full text |Cite
|
Sign up to set email alerts
|

Neural indicators of food cue reactivity, regulation, and valuation and their associations with body composition and daily eating behavior

Abstract: Exposure to food cues activates the brain’s reward system and undermines efforts to regulate impulses to eat. During explicit regulation, lateral prefrontal cortex activates and modulates the activity in reward regions and decreases food cravings. However, the extent to which between-person differences in the recruitment of regions associated with reward processing, subjective valuation and regulation during food cue exposure—absent instructions to regulate—predict body composition and daily eating behaviors i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…We conducted secondary analyses on data that were collected as part of two separate projects (n = 31, n = 75) that tested independent hypotheses pertaining to brain-behavior relationships in the eating domain that have been previously reported (Cosme & Lopez, 2020;Lopez et al, , 2014Lopez et al, , , 2017. Since we are using secondary data, the current study design was not preregistered; however, we preregistered the analytical plan for this particular paper prior to conducting any analyses (https:// osf.…”
Section: Statement Of Transparencymentioning
confidence: 99%
“…We conducted secondary analyses on data that were collected as part of two separate projects (n = 31, n = 75) that tested independent hypotheses pertaining to brain-behavior relationships in the eating domain that have been previously reported (Cosme & Lopez, 2020;Lopez et al, , 2014Lopez et al, , , 2017. Since we are using secondary data, the current study design was not preregistered; however, we preregistered the analytical plan for this particular paper prior to conducting any analyses (https:// osf.…”
Section: Statement Of Transparencymentioning
confidence: 99%
“…Although it is not a given that psychological modularity necessitates neural modularity, this assumption has been preserved in many neuroscientific implementations of system-based theories (Strang et al, 2013;Shulman et al, 2016), despite evidence in adults that multivariate patterns reflect meaningful information about decision-making (Hampton and O'Doherty, 2007). Our univariate and multivariate results, somewhat surprisingly, provide support for both modularity and population coding, respectively (Cosme and Lopez, 2020); specifically, results revealed that univariate NAcc and lPFC activity was associated with decision behavior, and also that PE of a multivariate cognitive control (but not value) signature predicted decisions. The former (evidence of modularity) is surprising, given the limited support for neural modularity that prior studies have found (Erickson, 2001), whereas the latter (population coding) is notable because no prior studies, to our knowledge, have found evidence of such in the context of brain modeling decision behavior (i.e., using multivariate metrics to model behavior/cognition).…”
Section: Implications For System-based Theories Of Adolescent Decisio...mentioning
confidence: 53%
“…In other words, the multivariate patterns code for a given psychological process, whereas the univariate activity of the modules controls the intensity of the process. Indeed, such multidimensional coding schemes appear to support decision behaviors in monkeys (Zhang et al, 2019), and similar findings from human samples in other domains (eating behavior) further hint at the neural plausibility of a modular-population hybrid scheme (Cosme and Lopez, 2020). Further work could also examine whether there is a qualitative shift between coding schemes across development (Gee et al, 2013).…”
Section: Implications For System-based Theories Of Adolescent Decisio...mentioning
confidence: 56%
See 1 more Smart Citation
“…Despite not being completely comprehensive, this approach still allowed for thorough investigation into the robustness of results. For all multiverse analyses, we constructed specification curves by ranking models by their beta estimates (ascending) for parameters of interest for interpretation and visualization (Cosme & Lopez, 2020;Klapwijk et al, 2019;Orben & Przybylski, 2019;Simonsohn et al, 2015Simonsohn et al, , 2020. Because specification choices were not preregistered, we did not conduct formal null hypothesis testing of specification curves.…”
Section: Multiverse Analyses and Specification Curvesmentioning
confidence: 99%